Social media marketing and brand personality to brand loyalty with brand trust and brand equity as a mediator - Erma Wantini; Fetria Eka Yudiana (Indonesian Journal of Islamic Economics Research, 2021)
This study aims to determine the effect of social media marketing and brand personality on brand loyalty with brand trust and brand equity as intervening variables for Islamic bank customers. Data were collected by distributing questionnaires to 200 respondents of Islamic bank customers in Indonesia who were selected using the purposive sampling technique. Path analysis and the Sobel test were used to test the hypothesis of the relationship between variables. The results show that social media marketing, brand trust, brand equity partially have a positive and significant effect on brand loyalty. Meanwhile, brand personality is not significant to brand loyalty. The F test shows that social media marketing, brand personality, brand trust, and brand equity simultaneously positively and significantly affect brand loyalty. The Sobel test in path analysis shows that brand trust and brand equity can mediate the relationship between social media marketing and brand personality on brand loyalty.